Penentuan Gangguan Ionosfera Bergerak Menggunakan Data GPS - Abdullah, Mardina; Ahmad Faizal Mohd. Zain, Ahmad Faizal Mohd; Sabirin Abdullah, Sabirin; Hashim, Nurbaya Mohd; Ho, Yih Hwa (Penerbit UTM Press, 2007)
This study focuses on the determination of ionospheric disturbances over Malaysia using GPS (Global Positioning System) signals in order to have a better understanding of radio wave propagation. This is done by identifying the presence of Travelling Ionospheric Disturbance (TID) using GPS data. TID is one of the disturbances occuring in the ionosphere that is caused by solar activities. The important parameter taken into account is the Total Electron Content (TEC). The value of the rate of change of TEC, ΔTEC, is taken within a period of 15 minutes in order to detect the occurrences of TID. The data is taken from a GPS receiver stationed at the WARAS Center KUiTHHO, in Parit Raja, Batu Pahat (1°52’N, 103°06’E). The value of ΔTEC is compared based on the largest daily geomagnetic index, Kp index for 3 different days. Geomagnetic storms affect the ionospheric and the layer that is of interest is the F–layer of ionosphere. Results show that there is an occurrence of TID above the receiving station. Results also shows that there is a close correlation between the occurrence of TIDs and Kp values; a higher Kp index show an increase in the number of TIDs. However, more data need to be analysed in order to understand the variation of this disturbance to allow for space weather forecasting in the near future.